Implementasi Praktikum Cahaya pada Pembelajaran IPAS untuk Mendukung Pemahaman Konsep Peserta Didik Kelas V Madrasah Ibtidaiyah Salafiyah Gapuro Batang - Zida Farah Nabila; Nabila Olivia; Mohammad Azrir Rizqi; Muhamad Aldo Syahputra; Putri Rahadian Dyah Kusumawati (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2026)
IPAS instruction in the Merdeka Curriculum emphasizes the scientific process through hands on learning experiences, one of which is through laboratory activities. Observations at MIS Gapuro indicate that students in Class 5-A have studied the theory of light but have never conducted a laboratory experiment. This study aims to describe the implementation of the light laboratory experiment in IPAS instruction, students’ understanding of the concept of light after the experiment, as well as the factors supporting and hindering its implementation. The study employed a descriptive qualitative approach with a sample of 28 fifth-grade students from Class V-A at MIS Gapuro. Data were collected through observation, interviews, documentation, and Student Worksheets (LKPD), then analyzed using data reduction, data presentation, and conclusion-drawing techniques. The results showed that the laboratory experiment was conducted through material presentation, group division, conducting experiments using simple tools and materials, and completing the Student Worksheets. Laboratory experiments help students understand the properties of light—namely, that light travels in a straight line, is reflected, and is refracted—based on direct observations. Supporting factors include student enthusiasm, the use of simple tools and materials, and worksheets, while inhibiting factors include time constraints, technical issues with learning media, and group dynamics. This study shows that simple laboratory experiments can support more meaningful science learning through direct scientific experiences.Keywords - Conceptual Understanding, Elementary School, IPAS Learning, Light Lab, Merdeka Curriculum